2018
DOI: 10.3389/fneur.2018.01135
|View full text |Cite
|
Sign up to set email alerts
|

Electrical, Hemodynamic, and Motor Activity in BCI Post-stroke Rehabilitation: Clinical Case Study

Abstract: The goal of the paper is to present an example of integrated analysis of electrical, hemodynamic, and motor activity accompanying the motor function recovery in a post-stroke patient having an extensive cortical lesion. The patient underwent a course of neurorehabilitation assisted with the hand exoskeleton controlled by brain-computer interface based on kinesthetic motor imagery. The BCI classifier was based on discriminating covariance matrices of EEG corresponding to motor imagery. The clinical data from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Significant gains in hand function were found for the FMA, ARAT and Jebsen-Taylor Test, after 7-10 weeks of training. This protocol was previously used by their group for training patients post-stroke in multiple studies [86][87][88]. The second study in CP [89] showed a decrease (improvement) in a serial reaction time task with the non-dominant hand, after only three sessions of BCI-NFT (8 min each) using visual feedback.…”
Section: Discussionmentioning
confidence: 99%
“…Significant gains in hand function were found for the FMA, ARAT and Jebsen-Taylor Test, after 7-10 weeks of training. This protocol was previously used by their group for training patients post-stroke in multiple studies [86][87][88]. The second study in CP [89] showed a decrease (improvement) in a serial reaction time task with the non-dominant hand, after only three sessions of BCI-NFT (8 min each) using visual feedback.…”
Section: Discussionmentioning
confidence: 99%
“…The technology of motor imagery-based on BCI has been used as a treatment for rehabilitation of post stroke and spinal cord injury patients as well as of the individuals with musculoskeletal disorders [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Particular attention is paid to training methods [7,12,18], the use of exoskeletons [9][10][11] and augmented and virtual reality [19,20]. However, the use of BCI in rehabilitation is restricted due to BCI-illiteracy phenomenon: about 10-30% of users cannot control BCI [21].…”
Section: Introductionmentioning
confidence: 99%
“…Brain-computer interface (BCI) is a soft-and hard-ware complex that allows to control external technical devices directly by signals of the brain without commonly used muscle activity. In recent years, motor imagery based BCI systems have become widespread in the motor rehabilitation of patients after a stroke or a trauma [1,10,21,22]. However, as shown [16], BCI technology yields great benefits not only for practical application, but it can also make a major contribution to brain research.…”
Section: Introductionmentioning
confidence: 99%